The Vacuum Device for Receiving Coatings on the Inner Surface of the Pipes by Magnetron Sputtering - Kolomiets, V.M.; Shkurat, O.I.; Kravchenko, S.M.; Lopatkin, R.Yu.; Chyzhov, I.G.; Samoilov, P.Ye.; Pavlenko, Yu.A.; Melnyk, M.O.; Honcharenko, O.I. (Science and Innovation, 2024)
Introduction. Due to the mechanical and chemical wear of the inner surfaces of the tubular products, there is a need to create protective coatings for these surfaces, which will increase the life of such products in various industries. Problem Statement. When designing equipment to obtain high-quality protective coatings on the inner surface of pipes, there are some difficulties associated with space limitations. Plasma sputtering with cylindrical magnetrons is widely used in the world. however, the questions about improving the sputter equipment to increase its efficiency and to improve the physical and mechanical properties of the coatings are current interest. The need of manufacturing universal equipment for processing of different diameter pipe products of is also urgent. Purpose. Development and creation of the test bench magnetron sputtering system for deposition coatings on the inner surfaces of pipe products with a diameter of 30 mm using the method of high-power impulse magnetron sputtering. Materials and Methods. The design elements of the magnetron sputter are made of stainless steel with a roughness not greater than Ra 2.5. The method of high-power impulse magnetron sputtering (HIPIMS) was used in the experiments. Results. The design documentation for the magnetron sputtering system has been developed. The stand for deposition of the protective coatings on the inner surface of pipe products with a diameter of 30 mm has been manufactured. using created cylindrical magnetron sputtering system may be realized in one technological cycle as to ionic cleaning internal surface of tubes and as to deposition new coatings. Conclusion. The prospects for creating the industrial equipment to solve the urgent problem of obtaining the quality coatings inside the pipes have been confirmed by positive results during the magnetron sputtering system prototype tests.